2012
DOI: 10.1371/journal.pone.0030108
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Male Pheromone on Rock Substrates Attracts Female Rock Lizards to the Territories of Males: A Field Experiment

Abstract: BackgroundMany animals produce elaborated sexual signals to attract mates, among them are common chemical sexual signals (pheromones) with an attracting function. Lizards produce chemical secretions for scent marking that may have a role in sexual selection. In the laboratory, female rock lizards (Iberolacerta cyreni) prefer the scent of males with more ergosterol in their femoral secretions. However, it is not known whether the scent-marks of male rock lizards may actually attract females to male territories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 74 publications
(124 reference statements)
1
21
0
1
Order By: Relevance
“…However, despite our results revealing heterogeneous trajectories of diversification across compounds and across species, we also observed that, as it would be expected, some of the compounds show a degree of coordinated evolution, revealing patterns of parallel evolution across lineages. This fact would be especially expected in components such as cholesterol, cholesta‐5,7‐dien‐3‐ol, ergosterol, and α‐tocopherol, given that their relative proportions in the scents are mediated by physiological trade‐offs arising from the high costs involved in their production (Kopena et al., 2011; Martín & López, 2006d, 2007, 2012, 2015). Therefore, physiological costs to allocate high abundances of some compounds to secretions could influence the allocation of high amounts of other chemicals, thus leading to the emergence of the above‐mentioned trade‐offs as the basis for some form of “chemical conflict” among compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite our results revealing heterogeneous trajectories of diversification across compounds and across species, we also observed that, as it would be expected, some of the compounds show a degree of coordinated evolution, revealing patterns of parallel evolution across lineages. This fact would be especially expected in components such as cholesterol, cholesta‐5,7‐dien‐3‐ol, ergosterol, and α‐tocopherol, given that their relative proportions in the scents are mediated by physiological trade‐offs arising from the high costs involved in their production (Kopena et al., 2011; Martín & López, 2006d, 2007, 2012, 2015). Therefore, physiological costs to allocate high abundances of some compounds to secretions could influence the allocation of high amounts of other chemicals, thus leading to the emergence of the above‐mentioned trade‐offs as the basis for some form of “chemical conflict” among compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Males of most lizard species are equipped with a series of epidermal glands located in the dermis of the inner thighs, which secrete waxy substances through pore‐bearing scales (Figure ), or ‘epidermal (femoral) pores’ (Mayerl, Baeckens, & Van Damme, ). The lipophilic compounds within the epidermal gland secretions are generally considered to be the leading source of chemical signals involved in lizard communication, and mediate behaviour in a variety of contexts (reviewed by Martín & López, ; Mayerl et al., ; but see Alberts, Phillips, & Werner, ), such as territory demarcation and assessment (Aragón, López, & Martín, ; Font, Barbosa, Sampedro, & Carazo, ; Leu, Jackson, Roddick, & Bull, ; Martín & López, ; Martins, Ord, Slaven, Wright, & Housworth, ), male rival assessment (Carazo, Font, & Desfilis, ; Hews, Date, Hara, & Castellano, ; Khannoon et al., ; López & Martín, ), female choice (Carazo, Font, & Desfilis, ; Gabirot, López, & Martín, ; Kopena, López, & Martín, ; Kopena et al., ; Martín & López, , ), assessment of female reproductive status (Cooper & Pèrez‐Mellado, ; Thomas, ), individual recognition (Alberts, ; Alberts & Werner, ; Gabirot, Castilla, López, & Martín, , ), sex identification (Cooper & Steele, ; Cooper & Trauth, ; Khannoon, Breithaupt, El‐Gendy, & Hardege, ) and species recognition (Barbosa, Font, Desfilis, & Carretero, ; Gabirot et al., ; Labra, ). Lizards passively mark or deposit these gland secretions into the environment while moving through their habitat, or they exhibit active marking behaviour to leave scent‐marks on the substrate of their choice (de Villiers, Flemming, Mouton, & Le, ; Mason & Parker, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, massive algae growth related to eutrophication increased the time and energy spent by Gasterosteus aculeatus males in courtship, while at the same time, relaxed the strength of selection in the male red courtship coloration (Candolin, Salesto, & Evers, 2007). Similarly, increased volatility and reduced permanency of scent marks may decrease the information that receivers can gain from chemical signals, reducing their ability to assess male quality (Martín & López, 2012). In such cases, females would approach male territories indiscriminately, potentially relaxing the strength of sexual selection on chemical signals and the male qualities that they advertise.…”
Section: Discussionmentioning
confidence: 99%